(untitled) (Revista Apotheke, 2024)
Interview with São Paulo artist Mauricio Parra, born in 1976, about traditional support preparations for oil painting, using rabbit skin glue, Gilders Clay Base and plaster of Paris. The interview, carried out online in August 2023, went beyond the pre-defined questions, better detailing the artist’s journey, with the first contact via Instagram, followed by Whatsapp, then transcribed by the Author. The information collected constituted a database to support the teaching internship of the Author of this article. To illustrate and complement the understanding of the data collected from the interview, the video indexed on the YouTube channel, prepared by Camilla Loreta, was used as a teaching resource. In the video, you can see the Artist step by step in preparing the wooden supports for his paintings.